The Eucharist as a Sacrament of Mission - Spencer, Stephen (Ecclesiology, 2025)
This study explores the ways that the Eucharist can be seen to express the missiological life of the church. The article first tells the story of the evolution of the Five Marks of Mission, a description of Christian mission which is now widespread among the churches of the Anglican Communion and beyond. This story shows a shift in the way the nature of the church and its activities are understood and so uncovers certain ecclesiological indicators. The Eucharist as practised in this tradition is then examined to uncover ways in which it expresses these indicators. Various human actions within the liturgy are found to do this, showing that the Eucharist not only points to the Five Marks of Mission but can be seen to be an active embodiment of them and so properly be described as a sacrament of mission.